Overall Dietary Quality Relates to Gut Microbiota Diversity and Abundance - Laitinen Kirsi; Mokkala Kati (My University, 2022)
Disturbances in gut microbiota homeostasis may have metabolic consequences with potentially serious clinical manifestations. Diet influences the host’s metabolic health in several ways, either directly or indirectly by modulating the composition and function of gut microbiota. This study investigated the extent to which dietary quality is reflected in gut microbiota diversity in overweight and obese pregnant women at risk for metabolic complications. Dietary quality was measured by a validated index of diet quality (IDQ) and microbiota composition was analyzed using 16SrRNA gene sequencing from 84 women pregnant less than 18 weeks. The alpha diversity, measured as Chao1, observed operational taxonomic units (OTUs), phylogenetic diversity, and the Shannon index were calculated. The IDQ score correlated positively with the Shannon index (rho = 0.319, p = 0.003), but not with the other indexes. The women who had the highest dietary quality (highest IDQ quartile) had higher gut microbiota diversity in all the investigated indexes, when compared to the women with the lowest dietary quality (lowest IDQ quartile; p < 0.032). Consequently, a higher dietary quality was reflected in a higher gut microbiota diversity. The presented approach may aid in devising new tools for dietary counseling aiming at holistic health, as well as in microbiome studies, to control for dietary variance